(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article presents some characteristics of linguocultural euphemisms used by male and female members of Uzbek and English society. It shows that there are some similarities and differences, which can be attributed to cultural and religious beliefs and values. Knowing and perceiving objects and events in reality is a structured activity that involves several logical-spiritual actions. In order to understand this activity, the science of cognitology, which emerged in the 19th century as a unique field in linguistics, plays an important role. With the help of cognitive linguistics, which is an integral part of cognitology, we can scientifically study the events that take place in our thinking. If we study euphemisms, which are considered to be a factor in the development of a society’s culture, through cognitive analysis, we will get a glimpse of their essence and meaning.